Analisis Kemampuan Penalaran Matematis Berbasis PISA Konten Bilangan pada Siswa Kelas VIII Semester Genap MTs Filial Popongan Tahun 2015/2016 - Mumpuni, Puput Sukmasari, Prof. Dr. Budi Murtiyasa, M.Kom (2016)
This reseacrh aimed to describe the reasoning ability, reasoning ability level and the percentage of students in solving mathematics based PISA the content of quantity. This research is a qualitative descriptive. The subjects of research were VIII C grade students of MTS Filial Popongan totaling 21 students. The data collection techniques using the test, interview and documentation. Data analysis technique conducted in stages of data reduction, data presentation, verification and conclusion. Analysis framework was developed based on the indicators and the level of students' reasoning. Indicators reasoning abilities of students in the research are filed allegations, perform mathematical manipulations, draw conclusions from a statement, check the validity of an argument. The result showed that the indicators that have the highest average is a mathematical manipulation. Level reasoning skills students classified as sufficient. Percentage of students' reasoning skills to solve problems based on the content of PISA quantity for the category of less that 23, 81%, while for enough category 57, 14%, while for both categories is 19, 05%.